Distributed micro-grid dispatching method - ZHANG ZITAO; XU YANG; QIN CHUAN; WEI QI (2021)
The invention relates to a distributed micro-grid dispatching method, which considers the regional distribution characteristics of power generation and energy storage resources in a micro-grid and the differentiated economic and environmental appeals of different subjects such as renewable energy power generation and energy storage. The method comprises the following steps: firstly, the structural composition of the micro-grid and economic and environmental appeals of each unit are analyzed; secondly, a micro-grid energy management model is established based on an equal-cost micro-increasing rate criterion, and the micro-grid energy management model comprises a target function and constraint conditions of micro-grid energy management; according to the method, the power generation cost and the pollutant discharge amount in the micro-grid system dispatching process are comprehensively considered, and the novel micro-grid dispatching method is designed to achieve the maximum economic benefits and the maximum env